Pengaruh Program Gerakan Literasi Sekolah dan Penggunaan Smarthphone Terhadap Minat Baca Siswa - Sri Adinda Finishi; Friyatmi Friyatmi (Jurnal Ecogen, 2023)
This  study objectives to find out the influence of school literacy movement program and smartphone use on student reading interest in SMKN 2 Padang. Sample from this study were 97 respondents who were students at SMKN 2 Padang. Based on the   partial t test, it can be determined that the variable of school literacy movement and smartphone usage has a significance value of 0,000 < 0.05, The conclusion is that the variables of school literacy movement and the use of smartphones have a positive and significant influence on students' reading interests. Based  on  the  simultaneous  f  test,  it  is obtained a significance value of   0.000 < 0.05, the conclusion of the school literacy movement program and the overall use of smartphones had a significant influence on student reading interests. The amount of influence of the independent  variable  on  the  dependent  variable  is 69.6%,  the  remaining  30.4%  is  influenced  by  variables other than the research model.